The Role of ASEAN as a Regional Governance Actor in the Conflict Resolution between Thailand and Cambodia: The Preah Vihear Temple Dispute, 2008–2011 - Savira Lukmana; Zakaria Anton Wicaksono (Universitas Wahid Hasyim Semarang, 2026)
ABSTRACT This research aims to discuss the role of ASEAN as a regional institution, where this role was implemented in an effort to resolve the conflict that occurred between Thailand and Cambodia in 2008-2011. What is quite unique is that this conflict is basically cultural in nature because it is a dispute over the area around the Preah Vihear Temple which has an area of ​​around 4.6 square km, where the area is the direct border between Thailand and Cambodia. Based on this, a transformation occurred which was initially a cultural problem. However, it later became a conflict on a regional scale, because this conflict had the potential to disrupt stability in the Southeast Asia region. Using a conflict resolution theory approach from Ralf Dahrendolf regarding the methods used to resolve the Preah Vihear Temple dispute between Thailand and Cambodia. ASEAN as a supranational organization at regional level is expected to be able to resolve the conflict between Thailand and Cambodia, including involving its member countries as mediators in the conflict. Keywords: ASEAN Role, Preah Vihear Temple, Thailand - Cambodia Conflict, Conflict Resolution